Association Rule Mining of Consumer Behavior at MOY Supermarket Using Apriori Algorithm - Alifah, Amalia Nur (ULTIMATICS, 2025)
MOY Frozen Food is a retail business located in Kediri Regency, specializing in the sale of frozen food, beverages, and basic necessities. In recent years, the retail industry has faced numerous challenges, including shifts in consumer behavior, technological advancements, and increasing competition. This study addresses the issue of identifying which products are frequently purchased together and determining appropriate recommendations for consumers. To achieve this goal, association rules are employed to discover correlations and co-occurrences among data sets, which facilitate the identification of product relationships within a single transaction. Using the Apriori algorithm with a minimum support threshold of 0.01 and a confidence level of 0.5, implemented in Python, this research successfully generates association rules. The insights derived from these association rules can be leveraged to develop various sales strategies, ultimately enhancing product sales at MOY Frozen Food.